Magnetic field curvature and poloidal Calculations using single field MHD plasma in Tokamak systems - Alhasi, Awad (Libyan Journal of Science &Technology, 2022)
In this paper, the magnetic field curvature and the poloidal , for single fluid magneto-hydrodynamic (MHD) plasma expressions are derived. To simplify the approach, we adhere to plasmas, with a circular cross-section. Thus we use the geometry of the torus, where is in the toroidal direction and is in the poloidal direction